2011
DOI: 10.1097/sap.0b013e3181d6e28a
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Mastopexy and Lateral Intercostal Artery Perforator (LICAP) Flap With Pectoralis Muscle Sling for Autologous Tissue Breast Augmentation in the Bariatric Patient

Abstract: Breast contouring surgery after massive weight loss is challenging because of unfavorable features such as inelastic skin, volume depletion, loss of upper pole fullness, and significant ptosis. An approach is presented for autoaugmentation using a lateral intercostal artery perforator (LICAP) flap secured with a pectoralis muscle sling, along with mastopexy based on vertical scar principles. In a total of 8 patients (average age: 39.3 years, range: 29-57; average body mass index: 30.8 kg/m2, range: 25.7-39.1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…6 Extended fasciocutaneous flaps may be designed, taking advantage of large intercostal perforators often present in MWL patients, to perform autologous mastopexy augmentation safely and reliably while simultaneously improving circumferential upper body contour. [5][6][7] Lateral intercostal artery perforators are based on the costal segment, and can facilitate design of a shorter flap for use in mastopexy. Both options minimize the donor-site morbidity attached to myocutaneous flap reconstructions requiring sacrifice of underlying muscles such as the latissimus dorsi.…”
Section: Discussionmentioning
confidence: 99%
“…6 Extended fasciocutaneous flaps may be designed, taking advantage of large intercostal perforators often present in MWL patients, to perform autologous mastopexy augmentation safely and reliably while simultaneously improving circumferential upper body contour. [5][6][7] Lateral intercostal artery perforators are based on the costal segment, and can facilitate design of a shorter flap for use in mastopexy. Both options minimize the donor-site morbidity attached to myocutaneous flap reconstructions requiring sacrifice of underlying muscles such as the latissimus dorsi.…”
Section: Discussionmentioning
confidence: 99%
“…This is an inferior pedicle technique used primarily for aesthetic purposes. Subsequently to Ribeiro's technique, other no-implant breast reshaping techniques were described, but all of them determined incisions to the breast parenchyma (13,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) (Table 6). In addition, several articles have claimed to increase upper pole fullness or breast projection without an implant.…”
Section: Discussionmentioning
confidence: 99%
“…The superomedial technique also allows plication of the medial and lateral pillars with the benefits of a vertical mammoplasty technique [12]. Kim et al recently showed minimal complications and high patient satisfaction using a superior pedicle autoaugmentationmastopexy technique [13]. Since this technique does not bring in tissue from outside the breast, patients who have insufficient breast volume and still desire upper pole fullness will require implant augmentation or alternative techniques.…”
Section: Discussionmentioning
confidence: 99%
“…The superomedial technique has been shown to be both safe and reliable with an acceptable complication rate [3,13]. Appropriate flap design with maximizing blood flow will limit the incidence of complications such as tip necrosis.…”
Section: Discussionmentioning
confidence: 99%